2011
DOI: 10.1002/0471140856.tx0437s48
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Reduction by Cytochrome P450

Abstract: This protocol describes the procedure for measuring the relative rates of metabolism of the α,β-unsaturated aldehydes, 9-anthracene aldehyde (9-AA) and 4-hydroxy-trans-2-nonenal (4-HNE); specifically the aldehyde reduction reactions of cytochrome P450s (CYPs). These assays can be performed using either liver microsomal or other tissue fractions, spherosome preparations of recombinant CYPs, or recombinant CYPs from other sources. The method used here to study the reduction of a model α,β-unsaturated aldehyde, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The differences in fluorescence emission wavelengths and the differential extraction with ethyl acetate allows for measurement of both the carboxylic acid and alcohol products in a single assay procedure as described by Amunom et al . 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in fluorescence emission wavelengths and the differential extraction with ethyl acetate allows for measurement of both the carboxylic acid and alcohol products in a single assay procedure as described by Amunom et al . 23 .…”
Section: Resultsmentioning
confidence: 99%
“…The emission wavelengths for both 9-A-MeOH and 9-A-MeOH were strikingly different, thus allowing measurement of these products in organic extracts from either acidified or alkalinized incubation reactions using appropriate standard curves for the two fluorescent products, respectively. 23 For example, 9-A-MeOH was measured in the ethyl acetate phase after raising the pH of the microsomal reaction mixture with a base. The fluorescence intensity of 9-anthracene methanol was found to be highest in this organic phase after a single extraction step, demonstrating the high extraction efficiency of 9-A-MeOH into the ethyl acetate organic phase (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the well-established oxidation reaction, the reduction reaction catalyzed by CYP has not been characterized in detail. The stoichiometry is written as: R X NADPH H RH XH NADP 55 . This reaction is mostly seen when the substrates contain quinones, azo-, halogenated, nitro-, N-hydroxy-, and hydroperoxide functional groups.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is mostly seen when the substrates contain quinones, azo-, halogenated, nitro-, N-hydroxy-, and hydroperoxide functional groups. Amunom et al 55,56 have reported that α,β-unsaturated aldehydes 9-anthracene aldehyde and 4-hydroxy-trans-2-nonenal are reduced/hydrogenated to their corresponding carboxylic acid by several human and murine CYP enzymes. They also identified that this CYP-dependent reduction occurred in the presence and absence of molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%